Protein Splicing of Inteins: A Powerful Tool in Synthetic Biology - Wang, Hao; Wang, Lin; Zhong, Baihua; Dai, Zhuojun (Frontiers in Bioengineering and Biotechnology, 2022)
Inteins are protein segments that are capable of enabling the ligation of flanking extein into a new protein, a process known as protein splicing. Since its discovery, inteins have become powerful biotechnological tools for applications such as protein engineering. In the last ten years, the development in the synthetic biology has further endow inteins with enhanced functions and diverse utilizations. Here we review these efforts.